The science and technology of civil engineering materials (Prentice-Hall, 1998)
The book offers a new approach, in which the science and technology are integrated. It is divided into four parts; the first two provide the general concepts of materials, referring to their fundamenbtal structure and mechanical properties. The other two parts of the book deal with specific construction materials.